Barriers of Supply Chain Intelligence practices in SMEs: case of Malaysia - Jaharuddin, Nor Siah; Mansor, Zuraina; Yaakob, Samsudin (Medwell Journals, 2016)
Frequent changes that occur in the contemporary global environment might pose a threat to Small and Medium Enterprises (SMEs) survival. SMEs are more fragile and facing higher competitiveness effect than large companies. They need Supply Chain Intelligence (SCI) which provides an analysis of the implications of marketplace change by detecting, anticipating and understanding the competitive environment and supply chain relationship that aids corporate leadership in strategic decisions. This study analyses the intensity of environmental competitiveness and barriers of intelligence activities by SMEs in the economy of Malaysia. The paper also analyses the internal and external dimensions challenges encountered by SMEs to ensure successful SCI implementation. The result is great significance because majority of business establishments are Small Medium Enterprises (SMEs) which directly affect the country in economic growth.